Transformation of Minangkabau Traditional Theatre in Contemporary Performance: Aesthetic and Dramaturgical Study - Edy Suisno (Melayu Arts and Performance Journal, 2025)
This study examines the transformation of Minangkabau traditional theatre in contemporary performance, with particular attention to aesthetic and dramaturgical changes in the adaptation of Randai as a folk theatre form. Randai has long been recognized as a performative expression that integrates kaba narrative, acting, dendang, music, silek-based movement, and circular staging patterns within the cultural order of Minangkabau society. However, contemporary theatre practices have opened new possibilities for reinterpreting these traditional elements through experimentation with space, body, visual composition, rhythm, and performance structure. This research aims to analyze how Minangkabau traditional theatre is transformed into contemporary performance and to identify the aesthetic and dramaturgical implications of such transformation. The study uses a qualitativedescriptive method with an interpretive approach. Data were collected through literature study, visual documentation from open sources, and textual analysis of scholarly sources related to Randai, traditional theatre, performance studies, and contemporary dramaturgy. The findings show that the transformation of Minangkabau traditional theatre occurs through the reconfiguration of narrative structure, the expansion of actor movement, the modification of musical functions, the reinterpretation of circular space, and the shifting position of tradition from communal representation to artistic exploration. These changes do not necessarily eliminate traditional identity; rather, they create a dialogic space between inherited cultural values and contemporary theatrical imagination. The novelty of this study lies in its effort to position the transformation of Minangkabau traditional theatre not merely as modernization, but as an aesthetic and dramaturgical negotiation that allows tradition to remain productive within contemporary performance discourse.